Penegakan Hukum Terhadap Pelaku Tindak Pidana Penimbunan Alat Kesehatan Pada Masa Covid-19 (Studi Di Kepolisian Resort Simalungun) - Sarmanto Simanihuruk (Universitas Islam Sumatera Utara, 2022)
The hoarding of medical devices by unscrupulous business actors creates a condition where the government and all officials jointly examine the causes of hoarding which results in availability becoming scarce and prices soaring high. The formulation of the problem in this thesis is how to regulate the law against the perpetrators of the crime of hoarding medical devices in the Covid-19 pandemic, what are the forms and modus operandi of the crime of hoarding medical devices in the Covid-19 pandemic at the Simalungun Police Resort, how are the obstacles and efforts of the Police in law enforcement? against the perpetrators of the criminal act of hoarding medical devices in the Covid-19 pandemic at the Simalungun Resort Police.The results of the study show that the legal arrangements for criminal acts of hoarding medical devices in the Covid-19 pandemic are regulated in Article 107 of Law Number 7 of 2014 concerning Trade which is the legal umbrella to ensnare perpetrators of hoarding medical devices during the covid-19 pandemic. The form and modus operandi of the criminal act of hoarding medical devices in the Covid-19 pandemic at the Simalungun Police Resort is to buy medical devices at a set price, then store and store them. Barriers to the Police in law enforcement against criminals hoarding medical devices in the Covid-19 pandemic at the Simalungun Police Resort are internal obstacles, namely the weak mentality of law enforcement officers and the lack of facilities and infrastructure in the investigation. External barriers, namely the lack of coordination between the local community and law enforcement, the suspect's statements are confusing. The efforts made by Simalungun Resort Police investigators in overcoming obstacles are approaching the community, coaching the community, training law enforcement officers to be firm, completing the facilities and infrastructure in the investigation,and giving severe sanctions to those who violate them, either ordinary people or the persons involved. Keywords: Law Enforcement, Medical Devices, Covid-19.